Filtration rate and remediation effectiveness of blood cockle (Tegillarca granosa) as a bioremediator of vannamei shrimp pond effluent - IHWAN IHWAN; RAJUDDIN SYAMSUDDIN; KHUSNUL YAQIN; DODY DHARMAWAN TRIJUNO; ANDI NIARTININGSIH; ABDUL HARIS; MUHAMMAD FARID SAMAWI; SRI WAHYUNI RAHIM; HASNI HASNI; YUNUS ANUGERAH SANI; SALWAN GHULAM; SITI MARIAM; HUSNUL KHATIMA; ALMUNAWAR ALMUNAWAR; MUTMAINNA ZALSABILA (Society for Indonesian Biodiversity, 2025)
Abstract. Ihwan, Syamsuddin R, Yaqin K, Trijuno DD, Niartiningsih A, Haris A, Samawi MF, Rahim SW, Hasni, Sani YA, Ghulam S, Mariam S, Khatima H, Almunawar, Zalsabila M. 2025. Filtration rate and remediation effectiveness of blood cockle (Tegillarca granosa) as a bioremediator of vannamei shrimp pond effluent. Biodiversitas 26: 3985-3993. The intensive culture of whiteleg shrimp (Litopenaeus vannamei) generates organic waste that can disrupt the balance of aquatic ecosystems. The blood cockle (Tegillarca granosa), a filter-feeding organism or bivalve remediation, has potential as a natural biofilter for remediating such waste. This study aimed to evaluate the filtration and bioremediation effectiveness of T. granosa on aquaculture waste from L. vannamei ponds, considering variations in size and density. Laboratory-scale experiments were conducted using a two-factor factorial design, with two levels of cockle size (2-3 cm and 4-5 cm) and two levels of density (15 and 30 individuals per 10 L, replicated three times for each level of density. Observed water quality parameters included Total Organic Matter (TOM), nitrite (NO?), nitrate (NO?), phosphate (PO?), and other physicochemical parameters. The results showed that T. granosa effectively remediated waste, with the highest TOM remediation rate of 24.49%, nitrate removal of 18.32%, phosphate removal of 21.67%, and COD removal of 26.75%, achieved at a size of 4-5 cm and density of 30 individuals per 10 L. The highest nitrite remediation effectiveness was achieved at a treatment size of 4-5 cm and a density of 15 individuals per 10 L. The filtration rate of T. granosa reached 4.71 mL/h in the treatment with a size of 4-5 cm and a density of 30 individuals/10 L. The optimal treatment was Treatment D. Therefore, utilizing T. granosa as a natural biofilter can be a sustainable strategy for managing intensive whiteleg shrimp pond waste, contributing to aquaculture sustainability and promoting water improvement, especially when size and density factors are carefully considered in its application. These findings highlight the potential of T. granosa as an effective biofilter species for integration into IMTA systems to enhance water quality and sustainability.